APLIKASI KULINER MOBILE DIKOTA SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2013)
Abstract - information has become a staple of Indonesian society is no exception people in the city of Semarang. One of the required information for the public, especially tourists at this time is the need of information relating to the culinary tourist spots available. So the purpose of designing Culinary Mobile Application in Android-Based Semarang is to facilitate the tourists to search culinary locations. From the results of this study will provide a Culinary Mobile Application in Semarang Based Android so that users can easily perform a search in culinary locations.In doing research approaches and methods need to perform system development methods. System approach used in this study is the approach to OOP (Object Oriented Programming). One tool or model to design-based software development OOP (Object Oriented Programming) is the UML. And in the implementation stages of system development, the author uses Prototype development system. Prototype is one of software development methods are widely used perangat.Applications built is very useful for enabling users to find information more quickly where culinary and efficiently. This application will be implemented to keep track of today's mobile technology platform, which is applied into the android platform.Keywords: Mobile Applications, Methods Prototype,